Comparative Plasma Exposure and Lung Distribution of Two Human Use Commercial Azithromycin Formulations Assessed in Murine Model: A Preclinical Study - Rivulgo, Virginia Margarita (2013)
Azithromycin(AZM)therapeutic failure and relapses of patients treated with generic -35 formulations have been observed in clinical practice.The main goal of this research was 36 to compare in a pre-clinical study the serum exposure and lung tissue concentrationof 37 two commercial formulations AZM-based in murine model. The current study involved 38 264 healthy Balb-C.Mice were divided in two groups (n=44): Animals of Group A 39 (Reference Formulation ?R-) were orally treated with AZM suspension at 10 mg/kg of 40 b.w.Experimental animals of Group B (Generic formulation ?G-) received identical 41 treatment than Group A with a generic formulation AZM-based.The study was repeated 42 twice as Phase II and III. Serum and lung tissue samples were taken 24 hpost treatment.43 Validated microbiological assay was used to determine the serum pharmacokinetic and 44 lung distribution of AZM.45 After the pharmacokinetic analysis was observed a similar serum exposure for both46 formulations of AZM assayed. In contrast, statistical differences (p< 0.001)were 47 obtained after comparing the concentrations of both formulations in lung tissue, being48 the values obtained for AUC and Cmax (AZM-R-)+1586 and 122%respectively,than 49 those obtained for AZM-G-in lung. These differences may indicate large differences on 50 the distribution process of both formulations, which may explain the lack of 51 efficacy/therapeutic failure observed on clinical practice.